2015
DOI: 10.1007/s00170-015-7837-0
|View full text |Cite
|
Sign up to set email alerts
|

Cutting signals analysis in milling titanium alloy thin-part components and non-thin-wall components

Abstract: Cutting signals can monitor the cutting status in metal cutting process such as acceleration, cutting force, motor current, and acoustic emission. In this paper, cutting force and spindle acceleration signals were analyzed and compared in milling titanium alloy thin-wall components and non-thinwall components under the same cutting parameters. Tool wear was analyzed during the whole cutting process. Frequency spectrum and wavelet analysis methods were used in this study to illustrate the impact of tool wear on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Similarly, Srinivasan et al [216], Tansel et al [204] and Lamraoui et al [95] reported that it is possible by using a single monitoring system to acquire signals from indirect sensors for simultaneous chatter detection and tool wear diagnosis, but the correlation between the two phenomena has not been widely revealed. In addition, diverse studies [264,[397][398][399][400][401][402] provided experimental results of the tool wear effect on the signal waveform and the energy distribution of the frequency bands, during the machining of different materials, as shown in Fig. 18.…”
Section: Multi-condition Monitoring and Identificationmentioning
confidence: 99%
“…Similarly, Srinivasan et al [216], Tansel et al [204] and Lamraoui et al [95] reported that it is possible by using a single monitoring system to acquire signals from indirect sensors for simultaneous chatter detection and tool wear diagnosis, but the correlation between the two phenomena has not been widely revealed. In addition, diverse studies [264,[397][398][399][400][401][402] provided experimental results of the tool wear effect on the signal waveform and the energy distribution of the frequency bands, during the machining of different materials, as shown in Fig. 18.…”
Section: Multi-condition Monitoring and Identificationmentioning
confidence: 99%
“…To further evaluate the de-noising effect of noise reduction, we conducted the frequency spectrum analysis to signals. The energy of vibration signal should be distributed at the integral multiples of the tooth passing frequency (TPF) [35].…”
Section: ) Vibrationmentioning
confidence: 99%
“…Zhou et al [10] studied the nonlinear dynamic behavior of cutting force during the machining process of thin plate parts, and the results indicate that the cutting force can develop complicated dynamic behavior due to the time-delay effect. Huang et al [11] used spectrum analysis and wavelet analysis to analyze and compare the cutting force and spindle acceleration signal between thin-walled and non-thin-walled titanium alloy parts to determine the influence of tool wear on cutting parts. Liu et al [12] proposed a finite-element-based milling error prediction method.…”
Section: Optimization Of Cutting Force and Error Compensationmentioning
confidence: 99%